2013
DOI: 10.3390/act2020019
|View full text |Cite
|
Sign up to set email alerts
|

Optically Driven Mobile Integrated Micro-Tools for a Lab-on-a-Chip

Abstract: This study proposes an optically driven complex micromachine with an Archimedes microscrew as the mechanical power, a sphere as a coupler, and three knives as the mechanical tools. The micromachine is fabricated by two-photon polymerization and is portably driven by optical tweezers. Because the microscrew can be optically trapped and rotates spontaneously, it provides driving power for the complex micro-tools. In other words, when a laser beam focuses on the micromachine, the microscrew is trapped toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Currently most of the works on TPP have been dedicated to developing the technique [10,11,12,13] and applying the technique to fabricate complex shaped microstructures [14,15,16], micro-machineries [17,18,19,20,21,22,23,24,25], micro/opto/electro-fluidic systems [26,27], and scaffolds for tissue engineering [28,29]. It has been demonstrated that a proper scaffold design and material stiffness can lead mesenchymal stem cells without osteogenic stimulation to differentiate towards osteogenic lineage [29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently most of the works on TPP have been dedicated to developing the technique [10,11,12,13] and applying the technique to fabricate complex shaped microstructures [14,15,16], micro-machineries [17,18,19,20,21,22,23,24,25], micro/opto/electro-fluidic systems [26,27], and scaffolds for tissue engineering [28,29]. It has been demonstrated that a proper scaffold design and material stiffness can lead mesenchymal stem cells without osteogenic stimulation to differentiate towards osteogenic lineage [29].…”
Section: Introductionmentioning
confidence: 99%
“…Optical tweezers can also be used to operate micromachines and have been shown to be capable of operating microscopic gears, rotors, levers, and motors among others. [24,[102][103][104] Mushfique et al demonstrated the use of optical tweezers for the operation of a pump in microfluidic channels while simultaneously using a holographic optical tweezer to measure the resulting fluid flow. [105] Experiments such as these demonstrate the potential of optical tweezers to drive and control entire lab-on-a-chip devices.…”
Section: Lab-on-a-chipmentioning
confidence: 99%
“…Furthermore, they also created a propeller that is able to rotate in a reserve direction if the relative position between optical focus and the propeller is changed . Liu et al also applied Archimedes microscrew as a driven tool for the microrotor ( Figure ) . In this study, when the microscrew was trapped and rotated using optical tweezer, the connected blades were driven together with a high efficiency of 1.9 rpm mW −1 .…”
Section: Applications Of Remotely Controllable Micromachines Fabricatmentioning
confidence: 99%
“…b) Scanning electron microscope (SEM) image for the as‐prepared micromachine. Adapted with permission . Copyright 2013, Multidisciplinary Digital Publishing Institute (MDPI).…”
Section: Applications Of Remotely Controllable Micromachines Fabricatmentioning
confidence: 99%